2011
DOI: 10.1111/j.1939-1676.2011.0760.x
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Myelopathy in a Bernese Mountain Dog with a Novel SOD1 Missense Mutation

Abstract: A n 8-year-old female spayed Bernese Mountain Dog (BMD) presented to the Bush Veterinary Neurology Service (BVNS) for paraparesis. The dog had been seen at the BVNS 13 months earlier for evaluation of progressive pelvic limb weakness. At that time, the dog had a short-strided gait in the pelvic limbs, mild postural reaction deficits in the right pelvic limb, normal segmental reflexes, and laxity of the right coxofemoral joint. The dog was treated with meloxicam (0.15 mg/kg PO q24h) for 3 days, amantidine (2 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 22 publications
2
58
0
3
Order By: Relevance
“…Homozygosity for the variant allele was associated with risk of developing DM in five dog breeds (17). A separate SOD1 missense mutation has been discovered in Bernese Mountain Dogs, but has only been detected in that specific breed so far (23,24). Biochemical characterization of the two canine SOD1 mutant proteins indicated the increased propensity to form protein aggregates with retained enzymatic activity, supporting a toxic gain-of-function role in canine DM similar to that role in human ALS (25).…”
Section: Significancementioning
confidence: 89%
“…Homozygosity for the variant allele was associated with risk of developing DM in five dog breeds (17). A separate SOD1 missense mutation has been discovered in Bernese Mountain Dogs, but has only been detected in that specific breed so far (23,24). Biochemical characterization of the two canine SOD1 mutant proteins indicated the increased propensity to form protein aggregates with retained enzymatic activity, supporting a toxic gain-of-function role in canine DM similar to that role in human ALS (25).…”
Section: Significancementioning
confidence: 89%
“…The resequencing of SOD1 from normal and DM-affected dogs revealed a c.118G >A missense mutation in exon 2 that predicted an E40K substitution (Awano et al, 2009). A homozygous c.52A > T missense mutation was more recently identified in the SOD1 gene in a Bernese Mountain Dog, which predicted a T18S substitution (Wininger et al, 2011) proposed to represent a spontaneous animal model of a SOD1-mediated human neurodegenerative disorder, namely amyotrophic lateral sclerosis (ALS) (Boillee et al, 2006). A recent study characterizing the biochemical properties of canine mutant SOD1 further indicated a strong link between SOD1-mediated diseases in humans and dogs (Crisp et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it is important to clarify the incidence of DM and identify other factors involved in the onset of DM. More recently, another novel DM-associated mutation was identified as c.52A>T (p.T18S) in a Bernese Mountain Dog [9], which is also known as a breed predisposed to DM [3,4]. Based on these observations, veterinarians should know that the genotyping assays for the c.118G>A mutation have application limits.…”
mentioning
confidence: 99%